Decisions, Decisions, Decisions: An Ethnographic Study of Researcher Discretion in Practice - van Drimmelen, Tom; Slagboom, M. Nienke; Reis, Ria; Bouter, Lex M.; van der Steen, Jenny T. (Science and engineering ethics, 2024)
This paper is a study of the decisions that researchers take during the execution of a research plan: their researcher discretion. Flexible research methods are generally seen as undesirable, and many methodologists urge to eliminate these so-called ‘researcher degrees of freedom’ from the research practice. However, what this looks like in practice is unclear. Based on twelve months of ethnographic fieldwork in two end-of-life research groups in which we observed research practice, conducted interviews, and collected documents, we explore when researchers are required to make decisions, and what these decisions entail. An abductive analysis of this data showed that researchers are constantly required to further interpret research plans, indicating that there is no clear division between planning and plan execution. This discretion emerges either when a research protocol is underdetermined or overdetermined, in which case they need to operationalise or adapt the plans respectively. In addition, we found that many of these instances of researcher discretion are exercised implicitly. Within the research groups it was occasionally not clear which topic merited an active decision, or which action could retroactively be categorised as one. Our ethnographic study of research practice suggests that researcher discretion is an integral and inevitable aspect of research practice, as many elements of a research protocol will either need to be further operationalised or adapted during its execution. Moreover, it may be difficult for researchers to identify their own discretion, limiting their effectivity in transparency.